THE RELATIONSHIP BETWEEN SOCIAL MEDIA USAGE INTENSITY AND EMOTIONAL REGULATION IN ADOLESCENTS - Abdulloh, Imron Habib; Yuliastuti, Estin; Suyatno, Suyatno (Jurnal Keperawatan, 2025)
Adolescence is often referred to as a transitional period from childhood to adulthood. In the digital era, social media usage has become a widespread phenomenon among adolescents, significantly influencing their emotional developmen. This study aims to determine whether there is a relationship between social media usage and emotional regulation in adolescents. This study used a quantitative correlational design with a cross-sectional approach. A total of 147 students were selected using total sampling. Data were collected using the Social Media Intensity Scale (SIPMS) and the Emotion Regulation Questionnaire (ERQ). Data were analyzed using Chi-Square statistical test. A significant relationship was found between social media usage intensity and adolescents’ emotional regulation (χ² = 28.694, df = 2, p < 0.001), indicating that heavier users tended to exhibit lower emotional regulation. There is a correlation between social media usage intensity and emotional regulation in adolescents. This suggests that excessive social media usage may negatively impact adolescents' emotional stability, emphasizing the need for proper management and regulation of social media use.